TINGKAT KUALITAS TIDUR MAHASISWA PRODI PENDIDIKAN OLAHRAGA UNIVERSITAS MUHAMMADIYAH KALIMANTAN TIMUR - Awang, Ahmad Zullian; Galih Priyambada (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2026)
This study aimed to describe the sleep quality of Physical Education students at Universitas Muhammadiyah Kalimantan Timur based on the Pittsburgh Sleep Quality Index (PSQI) Indonesian version. A descriptive quantitative cross-sectional design was applied to 34 non-athlete Physical Education students selected using purposive sampling. Sleep quality was assessed with the PSQI (global score 0–21), with good sleep quality defined as a total score ≤5 and poor sleep quality as >5. Data were analyzed descriptively using mean, standard deviation, and score range. The results showed that 25 students (73.5%) had good sleep quality and 9 students (26.5%) had poor sleep quality. Component scores indicated a mean of 1.18 (SD = 0.76; range 0–3) for subjective sleep quality, 2.29 (SD = 1.70; range 0–6) for sleep latency, 13.88 (SD = 3.37; range 0–14) for sleep duration, 9.79 (SD = 4.40; range 0–18) for sleep efficiency, 3.00 (SD = 0.76; range 0–3) for sleep disturbance, 0.29 (SD = 0.76; range 0–3) for sleep medication use, and 1.18 (SD = 0.76; range 0–3) for daytime dysfunction. These findings indicate that although most students are classified as good sleepers, relevant problems in sleep latency, duration, efficiency, and daytime dysfunction remain, suggesting the need for targeted sleep hygiene education and better alignment of study and training schedules to support sleep recovery.